Cell-autonomous regulation of cell and organ growth in Drosophila by Akt/PKB. - Verdu, J.; Buratovich, M.A.; Wilder, E.L.; Birnbaum, M.J. (Nature Cell Biology, 1999)
Organismal size is determined by a tightly regulated mechanism that coordinates cell growth, cell proliferation and cell death. The Drosophila insulin receptor/Chico/Dp110 pathway regulates cell and organismal size. Here we show that genetic manipulation of the phosphoinositide-3-OH-kinase-dependent serine/threonine protein kinase Akt (protein kinase B) during development of the Drosophila imaginal disc affects cell and organ size in an autonomous manner. Ectopic expression of Akt does not affect cell-fate determination, apoptosis or proliferation rates in imaginal discs. Thus, Akt appears to stimulate intracellular pathways that specifically regulate cell and compartment size independently of cell proliferation in vivo.